KAJIAN FENG SHUI TERHADAP TEMPAT USAHA DI JALAN RUMAH SAKIT, TASIKMALAYA - Ethan Abner Farrell Dauna; Dewi Mariana (Riset Arsitektur (RISA), 2024)
Abstract - All owners always wanted their business to go well, including those near hospitals, which had so negative energy that people would feel uncomfortable to be around for long. On Jl. Rumah Sakit, Tasikmalaya city, West Java province, there was a restaurant - RM Ny. King, which was on the opposite side of Dr. Soekardjo Hospital, but managed to maintain its business since the 1970s. There was also a 24-hour fried food vendor nearby and Kedai Bakso Solo Mas Wiji with T-junction position - a negative position according to Feng Shui - but both had lasted for more than two decades. Busy activities only seemed to occur where the three premises were, while others were not going well and mostly happened to pharmacies, which should have been able to sell well. This research was conducted to find out why only some businesses on Jl. Rumah Sakit (from in front of Kedai Bakso Solo Mas Wiji to RM King) were going well, according to Feng Shui studies, a knowledge that studied energy related to buildings. This research used the qualitative descriptive approach and tested all buildings in Jl. Rumah Sakit. For analysis, basic theories of Feng Shui, Form Theory, Five Elements Theory, Four Celestial Animals Theory, and Water Theory were used. In addition, Market Area Location Theory was also used to see the tendency of people to shop in the premises. It was concluded that the segment between Kedai Bakso Solo Mas Wiji until RM Ny. King had the most buildings that follows the Feng Shui theories used in this research. That is the reason why activities were more concentrated in this segment rather than others in Jl. Rumah Sakit. Keywords: Feng Shui, Business Places, Hospital